Sr-doped bioactive glasses for biological applications - Goudarzi, Zahra; Ijadi, Amir; Bakhtiari, Ameneh; Eskandarinezhad, Sara; Azizabadi, Negar; Asgari Jazi, Mohammadreza (Journal of Composites and Compounds, 2020)
In this work, sol–gel derived bioactive glasses (BGs) system of 60% SiO2-(36-x) CaO-4P2O5-x SrO (where x = 2, 4, 6 and 8 mol%) were obtained. The bioactivity and proliferation of G292 cells was investigated for Sr-containing BGs. X-ray diffraction analysis (XRD), Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were utilized to study the obtained phases, hydroxyapatite (HA) morphology, and its functional groups, respectively. The XRD and FTIR tests showed that the rate of hydroxyapatite formation on sample 2S was higher than that of other samples. Also 3-(4,5 dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay performed after one day revealed that the sample containing 6 mol% of Sr (6S) showed higher viability. However, the sample with 8 mol% Sr (8S) showed a decrease in bioactivity in osteoblast G292 cells proliferation. According to the results, 6S BG specimen with 6 mol% SrO exhibited appropriate bioactivity and cell proliferation. This finding showed that the obtained BGs could be potentially used for drug delivery systems as well as dental and orthopedic applications.